Linguistics as Semiotics. Saussure and Bühler Revisited. - Durst-Andersen, Per (Signs - International Journal of Semiotics, 2008)
The article identifies some fundamental problems with Sausure’s sign conception and with Bühler’s Organon Model, and presents two new sign and communication models, one for the speaker, the Grammatical Triangle, and another for the hearer, the Semiotic Wheel. It is argued that the arbitrariness of language makes its arsenal of words omnipotent and capable of referring to anything. Exactly because of its arbitrariness language must have a code that can give a semiotic direction to the otherwise completely static sign. The speaker’s model consists of an obligatory choice between three types of code corresponding to the three ways in which states of affairs exist: situations in a real or in an imagined world, the speaker’s experience or non-experience of them or the hearer’s experience or non-experience of them. The hearer uses his model as an information seeker in order to compensate for those pieces of content that were left out by the speaker’s choice of semiotic orientation.